Toward a better understanding of culture: wikis in the beginning German classroom. Issue 2 (3rd April 2017) - Ducate, Lara; Steckenbiller, Christiane
Abstract : The questions of how to teach culture, which culture(s) to teach and how to lead students to intercultural competence and understanding are common questions for language teachers. The current project employed wikis to systematically integrate culture and authentic texts into beginning German courses at a large south-eastern university in the United States. The study examined whether close readings of authentic texts on a variety of cultural topics from German-speaking countries, careful discussion and then a final analysis of the topics in the form of students' essays could lead to a deeper understanding of the cultures of German-speaking countries and possibly of one's own culture. During this study, students were actively engaged in analysing authentic cultural documents to learn more about the products, practices and perspectives of the target culture, including how these three aspects interact and connect, thereby improving their analytical skills and thinking more critically about their own culture. As indicated by a pre-/post-test serving as quantitative data, students did increase their cultural knowledge of German-speaking countries, mainly in their knowledge of practices, over the semester. Qualitative analyses of their final essays indicated that students also expanded their awareness of perspectives of the target culture and gained a deeper understanding of their own culture.